Heroic Measures: Just Bioethics in an Unjust World - Zoloth, Laurie (The Hastings Center report, 2001)
In its excitement over the quandries posed by biotechnology, bioethics is in danger of neglecting basic health care needs. What is needed is an understanding of ethics that emphasizes responsibility to others rather than rights.